IMPROVING THE STUDENTS’ LISTENING COMPREHENSION BY USING DISCUSSION WITH AUDIO-VISUAL MEDIA (VIDEO) - Christina Angelina; Amirudin Amirudin; Laksmy Ady Kusumoriny (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
This research focuses on the use of audio-visual media (video) to improve the students' listening skill for the seventh-grade students of SMP PGRI Curug in the academic year of 2019/2020. Aim of this study is to find out whether the use of audio-visual media (video) can improve the students‟ listening skill and how far the improvement in students listening skill by using audio-visual media (video). The method of this research is action research. The technique of data analysis is qualitative research. Each cycle comprises planning, acting, observation, and reflecting. The researcher stated that there is an improvement of students‟ listening skill using audio-visual media (video). It can be seen from the number of students who pass the passing grade (KKM) in cycle I and cycle II. The passing grade is 70. The result of a listening test in a pre- cycle without using video got an average score of 64,80 or 33 % of students to get a good score or the passing grade (KKM). In the cycle, I, the result of the listening test using video, got an average score of 71,07. or 66 % of students get a good score or the passing grade (KKM). The students were easier to listen to. Although they still found it difficult to focus while watching a video. The result of the listening test got better in cycle II. The students were more understanding in doing their activity using video. In this cycle, they got an average score of 76,93 or 100 % of students to get a good score or the passing grade (KKM).